Anthelmintic efficacy of five tropical native Australian plants against Haemonchus contortus and Trichostrongylus colubriformis in experimentally infected goats (Capra hircus) - Moreno, Fabiana Carina (2012)
The study of the anthelmintic properties of plants rich in plant secondary metabolites can provide ecologically sound methods for the treatment of parasites on grazing animals. The purpose of the present study was to evaluate the anthelmintic effect of five tropical native Australian plant species rich in plant secondary metabolites on adult Haemonchus contortus and Trichostrongylus colubriformis in experimentally infected goats. Thirty young, nematode-free goats were infected with 2500 H. contortus and 5000 T. colubriformis infective larvae thrice weekly for a week (day 1–7 of the experiment). On day 27 after first infection, the goats were allocated into six groups of five animals per group. From day 28 to day 35, fresh leaves from Acacia salicina, Acacia nilotica, Eucalyptus corymbia, Casuarina cunninghamiana and Eucalyptus drepanophylla were included in the goats diet. Five groups were offered leaves from one of these plant species and one group, the untreated control, received only the basal diet formulated with 20% Medicago sativa and 80% Avena sativa. Following plant material administration, the goats were monitored daily until day 40 and then slaughtered on day 41. Total faecal worm egg output, total production of larvae recovered from faecal cultures, total post-mortem worm burdens and the per capita fecundity of female worms were estimated. The toxicity of the plant species for the goats was measured by histopathological analyses of liver and kidney samples. Results showed that goats feeding on the plant material rich in plant secondary metabolites had significantly lower egg output compared to the control goats (P < 0.05). A similar response was found for larval production in both H. contortus and T. colubriformis supporting that egg output was affected in both species. Although the total worm burdens were not affected by the plant material (P > 0.05), the per capita fecundity was significantly reduced by E. corymbia, A. nilotica and A. salicina (P < 0.05). No signs of toxicity were detected in the liver or kidney samples. It is concluded that goats can benefit from the short-term ingestion of plant secondary metabolites, which reduce the total faecal egg output and thus decrease the potential for re-infection from the pasture.